Two more House Groups with Three-aisled Long-houses from the Early Bronze Age at Højgård, South Jutland - Ethelberg, Per (Journal of Danish Archaeology, 1991)
Two more House Groups with Three-aisled Long-houses from the Early Bronze Age at Højgård, South Jutland